Evaluation of the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of a Single Intravenous Dose of Miridesap in Healthy Japanese Subjects. Issue 5 (17th December 2018) - Ino, Hiroko; Doi, Yohei; Liefaard, Lia; Cookson, Louise; Chen, Chao; Itoh, Hiroshi; Igarashi, Harue; Nakano, Atsushi
Abstract: This phase 1 study characterized the safety, tolerability, pharmacokinetics, and pharmacodynamics of miridesap (GSK2315698) following an intravenous (IV) infusion in healthy Japanese men. Subjects in Cohort 1 received 1‐hour IV infusions of 10, 20, and 40 mg of miridesap or placebo, and subjects in Cohort 2 received a 15‐hour IV infusion of 20 mg/h of miridesap or placebo. No treatment‐related adverse events were reported. No new safety signals were identified for either vital signs or clinical laboratory parameters. A dose‐dependent increase was observed in miridesap exposure (area under the concentration‐time curve and maximum observed drug concentration) in the 10 to 40 mg/h dose range after a 1‐hour IV infusion of miridesap. Rapid depletion of circulating serum amyloid P component was observed after the initiation of miridesap infusion. Serum amyloid P component concentrations fell in a dose‐dependent manner following administration of miridesap.